KERAGAMAN GENETIK TIMOHO (Kleinhovia hospita Linn.) BERDASARKAN PENANDA RANDOM AMPLIFIED POLYMORPHISM DNA (RAPD) - ILG Nurtjahjaningsih; Lukman Hakim; Yemima Viktory Utomo; Anto Rimbawanto; AYPBC Widyatmoko (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2021)
Timoho (Kleinhovia hospita Linn.) has high economic value for medicine and construction. However, information on genetic diversity and conservation genetic have been limited by the lack of genetic data. Acacia mangium (mangium)This study aimed to assess genetic diversity of timoho using RAPD markers. Leaf samples of seedlings were collected from a nursery at CFBTI in Yogyakarta; the seedlings originated from plantation in Gunung Kidul (GK) and arboretum in Faculty of Forestry, GMU (FK). Seven out of 22 screened RAPD markers were stable in amplification and consisted of 61 polymorphic loci; then these markers were used to analyse genetic diversity and population structure of 48 seedlings from GK and FK. The genetic diversity and structure parameters were calculated by GenAlex software. A moderate level of genetic diversity (mean uHE=0,326) and great genetic distance between the two populations (DA=0.119) were found in this species. PCoA analysis showed that the 48 individuals were divided into two clusters according to their originated population. Appropriate conservation strategies were proposed to protect genetic diversity of this species.